Influence of Environmental Factors on Antagonism of Fungi by Bacteria in Soil: Nutrient Levels - Rosenzweig, William D. (1980)
The addition of 0.25, 0.5, or 1.0% glucose to a soil (K) amended with either 6% kaolinite (K6K) or montmorillonite (K6M) or the adjustment of the C/N ratio of the soils from 23/1 to 10/1 with NH(4)NO(3) eliminated the inhibition of Aspergillus niger by Serratia marcescens, regardless of whether the fungus and bacterium were inoculated into the same or separate sites in the soils. The adjustment of the C/N ratio to 15/1 or of the C/P ratio from 1,000/1 to 100/1 with KH(2)PO(4) did not eliminate the antagonism. However, with the higher glucose and NH(4)NO(3) amendments, S. marcescens died out in the K and K6K (but not in the K6M) soils, apparently due to reductions in pH that resulted from the increased metabolism induced by added nutrients. In soils amended with CaCO(3), S. marcescens did not die out, but the inhibition of A. niger by S. marcescens or Agrobacterium radiobacter was eliminated or reduced by the addition of glucose, but not of NH(4)NO(3), and was influenced by the clay mineralogy and pH of the soils. When NH(4)NO(3) was added to the soils adjusted with CaCO(3) to pH values above 6.0, growth of A. niger was inhibited, regardless of whether bacteria were present or not, as a result of the volatilization of NH(3). Bacillus cereus and another species of Bacillus did not inhibit A. niger under any of the environmental conditions. There was a direct correlation between the degree of inhibition and the rate of glucose utilization by the various bacteria, indicating that the antagonism of A. niger by some bacteria in soil was the result primarily of a competition for carbon and that this competition was influenced by other environmental factors, such as pH and clay mineralogy.